Differential expression of apolipoprotein D in male reproductive system of rats by high‐fat diet. (27th August 2016) - Lim, W.; Bae, H.; Song, G.
Summary: Apolipoprotein D, a 29‐kDa secreted glycoprotein that belongs to the lipocalin superfamily, is widely expressed in various tissues and associated with lipid metabolism as a component of high‐density lipoproteins. Although Apolipoprotein D binds to small hydrophobic ligands including cholesterol, little is known about effects of high‐fat diet with cholesterol on expression of Apolipoprotein D in the male reproductive tract. Therefore, we investigated Apod expression in penises, prostate glands, and testes from rats fed a high‐fat diet including a high amount of cholesterol. Our previous research indicated that a high‐fat diet induces dyslipidemia leading to histological changes and dysfunction of male reproduction in rats. Consistent with these results, Apod mRNA expression was significantly ( p < 0.001) decreased in penises and prostate glands ( p < 0.01) and testes ( p < 0.01) from rats fed a high‐fat diet as compared with normal diet. In addition, Apod mRNA and protein were detected predominantly in urethral epithelium and penile follicle from rats. Moreover, changes in expression of specific microRNAs ( miR‐229b‐3p, miR‐423‐3p, and miR‐490‐3p ) regulating Apod in the penises and prostate glands were negatively associated with Apod expression. Collectively, results of this study suggest that Apod is a novel regulatory gene in the male reproductive system, especially in penises of rats fed a high‐cholesterol diet, and that expression of Apod is regulated at the posttranscriptional level by target microRNAs.